ANTIBIOTIC RESISTANCE: STRATEGIES FOR COMBATING THE GLOBAL THREAT - S. Naveen Killai (PT. Radja Intercontinental Publishing, 2024)
Antibiotic resistance has emerged as one of the most pressing global health threats, jeopardising the efficacy of life-saving treatments and escalating healthcare costs. Misuse and overuse of antibiotics in human medicine, agriculture, and environmental practices have accelerated the emergence of resistant strains, leading to an estimated 1.27 million deaths annually. This resistance undermines the effectiveness of treatments for common infections, complicates medical procedures, and imposes significant economic burdens. This article explores the multifaceted nature of antibiotic resistance, examining its causes, consequences, and potential solutions. Strategies such as antimicrobial stewardship, stricter regulatory frameworks, and global surveillance systems are discussed as vital measures for combating resistance. The importance of research and development for new antibiotics and alternative therapies, including bacteriophage treatments, antimicrobial peptides, and vaccines, is emphasised as part of a comprehensive response. Furthermore, the article highlights the critical role of international collaboration and public-private partnerships in harmonising global efforts and addressing market failures in drug development. By integrating multidisciplinary approaches and fostering a global commitment, the threat of antibiotic resistance can be mitigated. This research underscores the urgency of immediate action to preserve the efficacy of antibiotics and safeguard the future of healthcare systems worldwide